Protective role of herbal formulation-divine noni against cisplatin-induced cytotoxicity in healthy cells by activating Nrf2 expression: An in-vivo and in-vitro approach - Mohammad Ali; SN Manjula; Shahid Ud Din Wani; Vipan K Parihar; KM Mruthunjaya; SubbaRao V Madhunapantula (Elsevier, 2021)
Background: Morinda citrifolia (Noni) is an herbal remedy with multiple therapeutic properties such as antioxidant, anticancer, anti-inflammatory, antihypertensive effects due to rich in phytochemical constituents. Purpose: To evaluate chemoprotective effect of noni in dipping cisplatin (CP)-induced cytotoxicity in normal (healthy) cells through an antioxidant activity using in-vitro and in-vivo. Methods: Chemoprotective study of fresh noni juice (NJ) and divine noni gold (DNG) at the doses (0.3125-10 mg/ml) were performed against CP (3.125-100 µM) induced cytotoxicity in normal cells (BEAS-2B) by Sulforhodamine B assay at 24 h and 48 h and the percentage of growth inhibition was calculated. Similarly, the protective effect of noni (360 mg/b.wt.) were investigated against CP (5 mg/ml) induced cardiotoxicity in healthy mice through the investigation of serum biochemical markers, endogenous antioxidant enzymes were interpreted. Finally, the chemoprotective mechanism of DNG was accomplished Nrf2 expression following CP challenged NIH-3T3 cells was performed by the western blot method. Results: Treatment with noni at tested dose exhibited the least toxicity in normal cells (BEAS-2B). CP at the following concentrations induced cell death in time and dose-dependent manner. Whereas, noni revealed a significant cytoprotective effect against CP-induced cytotoxicity in the normal cells. Further in in-vivo study, treatment with noni at 360 mg/b.wt in CP injected animals attenuated cardiac injury as indicated by quenching the activities of serum biochemical markers, alleviated enzymatic and non-enzymatic antioxidant enzymes. Furthermore, noni attenuated CP induced toxicity by indirect antioxidant activity were proved by Nrf2 expression. Conclusion: Results suggest that DNG is more potent than NJ. Findings confirmed that DNG protects against CP-induced toxicity by activating the Nrf2 expression. More studies are needed to comprehend the mechanisms of DNG cytoprotection.